2013
DOI: 10.1007/s13193-013-0243-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Splenic Lymphoma: A Case Report

Abstract: Primary splenic lymphomas (PSL) constitute a rare variety of splenic neoplasms. As a secondary lymphoid organ, the spleen is usually involved by lymphomas as part of the systemic illness. However, rarely it can be the exclusive site of disease burden. An elderly lady presented with symptoms and signs of splenomegaly. After evaluation she was found to have a splenic tumor. Splenectomy was done which revealed primary splenic lymphoma. This case report highlights the evaluation and management of this illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…They found no correlation between histological subtype and prognosis [ 6 ]. Splenic irradiation is also a treatment option for inoperable cases in order to reduce the size of the spleen [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no correlation between histological subtype and prognosis [ 6 ]. Splenic irradiation is also a treatment option for inoperable cases in order to reduce the size of the spleen [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relapse is a common problem with those who suffer from DLBCL, as 40% of those with DLBCL will eventually relapse [ 4 ]. Relapse could be diagnosed with whole body F-deoxyglucose (FDG) PET scan or a splenic biopsy [ 7 ]. Mondello et al conducted a retrospective study on 123 patients with relapsed or refractory DLBCL, which showed that lenalidomide at 25 mg/day is a superior therapeutic option than 15 mg/day and it is more effective in patients with non-germinal center B-cell DLBCL [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to spleen lymphoma diagnosis, ultrasound and CT are the modalities of choice. Four helical CT radiological patterns have been described for lymphoma 8 : -Homogeneous splenomegaly.…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…Con respecto al diagnóstico de linfoma de bazo; la ecografía y la TC son las modalidades de elección. Se han descrito cuatro patrones radiológicos de TC helicoidal para el linfoma 8 :…”
Section: Estudios Diagnósticosunclassified